116. Characterization of a commercial Optically Stimulated Luminescence (OSL) dosimetry system for VMAT treatments verifications. (December 2018) - Bonanno, E.; Amico, A.G.; Cavalli, N.; D'Agostino, A.; Girlando, A.; Pisasale, G.; Ricottone, N.; Marino, C.
Abstract : Purpose: A new commercial OSL dosimetry system was studied to analyze the possibility of its using for VMAT planning checks. The system was characterized and tested in conventional dose range (0, 25–3 Gy). Methods: NanoDots (Landauer®), matched with readout system MicroSTARii™, are made of Al2 O3 :C, which show sensitivity 40–60 times the TL one. The characterization included: signal decrease for repeated readings; angular, energy and dose-rate dependence. A calibration curve was obtained in range 0, 25–3 Gy, using RW3 slab phantom and 6 MV photon beam. A VMAT plan, regarding lung lesion, was designed and optimized with: 6 MV, 600 MU/min, Eclipse TPS and Acuros XB algorithm (13.6.23) for TrueBeam 2.5. Verification plans were created starting from the first one, both in RW3 and in anthropomorphic phantom. The measurement in RW3 was compared with the pin point measurement value. In anthropomorphic phantom, got in position using CBCT, the OSLDs were allocated in four apposite inserts, with different densities, both inside and outside the PTV. Results: The OSLDs, exposed to 1 Gy and read for 5 times, showed a maximum deviation from the 1nd reading of 2% with a variation coefficient of 0, 8%. In the range 0.25–3 Gy, the OSLDs exhibited a 2nd order polynomial fit with dose related to 6 MV energy. The 10 MV polynomial fit moved away from 6 MV one with increase of dose, but into error bars (Fig.). Angular dependence response presented a maximum deviation from the 0° angle reading of 2, 7%, corresponding at 270° angle. A dose-rate dependence was not found in the range 200–600 MU/min. The results of the comparison Pin Point VS OSLD VS TPS in RW3 and in anthropomorphic phantom are showed in the Table. Conclusions: The OSLD exhibited to be feasible for VMAT verifications in conventional fractionated treatments using 6 MV photon beams.